A synthesis of recent analyses of human resources for health requirements and labour market dynamics in high-income OECD countries. Issue 1 (December 2016) - Tomblin Murphy, Gail; Birch, Stephen; MacKenzie, Adrian; Bradish, Stephanie; Elliott Rose, Annette
Abstract Background Recognition of the importance of effective human resources for health (HRH) planning is evident in efforts by the World Health Organization (WHO) and the Global Health Workforce Alliance (GHWA) to facilitate, with partner organizations, the development of a global HRH strategy for the period 2016–2030. As part of efforts to inform the development of this strategy, the aims of this study, the first of a pair, were (a) to conduct a rapid review of recent analyses of HRH requirements and labour market dynamics in high-income countries who are members of the Organisation for Economic Co-operation and Development (OECD) and (b) to identify a methodology to determine future HRH requirements for these countries. Methods A systematic search of peer-reviewed literature, targeted website searches, and multi-stage reference mining were conducted. To supplement these efforts, an international Advisory Group provided additional potentially relevant documents. All documents were assessed against predefined inclusion criteria and reviewed using a standardized data extraction tool. Results In total, 224 documents were included in the review. The HRH supply in the included countries is generally expected to grow, but it is not clear whether that growth will be adequate to meet health care system objectives in the future. Several recurring themes regarding factors of importance in HRH planning were evident across the documents reviewed, such as aging populations and health workforces as well as changes in disease patterns, models of care delivery, scopes of practice, and technologies in health care. However, the most common HRH planning approaches found through the review do not account for most of these factors. Conclusions The current evidence base on HRH labour markets in high-income OECD countries, although large and growing, does not provide a clear picture of the expected future HRH situation in these countries. Rather than HRH planning methods and analyses being guided by explicit HRH policy questions, most of the reviewed studies appeared to derive HRH policy questions based on predetermined planning methods. Informed by the findings of this review, a methodology to estimate future HRH requirements for these countries is described.